Development of Calistung E-Book with Flora and Fauna Character in Indonesian and Mathematics Learning Grade I Muhammadiyah Purworejo Elementary School - Sariyati, Feni; Ratnaningsih, Arum; Pangestika, Rintis Rizkia (Jurnal Pendidikan Amartha, 2022)
This research is a research and development (Research and Development) using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were grade 1 students of SD Muhammadiyah Purworejo in the 2021/2022 academic year. Data collection techniques in this study were interviews, questionnaires, tests, and documentation. The instruments used are interview sheets, validation sheets, student response questionnaires. The results of the research carried out: (1) Produce the Calistung E-Book using the ADDIE model, (2) The feasibility of the product is obtained from the validity of getting a value of 3.44. Then the practicality of the student's response with a value of 3.75. (3) the effectiveness of the product is seen based on the results of the pre-test and post-test with an effectiveness percentage of 71.4%. Based on this study, it can be concluded that the E-Book Calistung with Flora and Fauna Characters developed in this study is categorized as very feasible and effective to be used as a learning medium in elementary schools